Role of bisphenol A as environmental factor in the promotion of non‐alcoholic fatty liver disease: in vitro and clinical study. Issue 6 (11th January 2018) - Dallio, M.; Masarone, M.; Errico, S.; Gravina, A. G.; Nicolucci, C.; Di Sarno, R.; Gionti, L.; Tuccillo, C.; Persico, M.; Stiuso, P.; Diano, N.; Loguercio, C.; et al.
Summary: Background: Bisphenol A is an endocrine disrupting chemical associated with type 2 diabetes mellitus (T2DM), cardiovascular disease and liver enzyme abnormalities. Aim: To evaluate bisphenol A plasma and urine levels in non‐alcoholic fatty liver disease (NAFLD) patients compared to healthy subjects. Furthermore, we evaluated, in human HepG2 cells, the effects of exposure to different concentrations of bisphenol A on both oxidative stress induction and cell proliferation. Methods: We enrolled 60 patients with histological diagnosis of NAFLD with or without T2DM and sixty healthy subjects. In vitro, the proliferation of bisphenol A‐exposed HepG2 cells at two different concentrations (0.025 and 0.05 μM) was evaluated, both at high (H‐HepG2) and at low (L‐HepG2) glucose concentrations for 48 h. Lipoperoxidation was assessed by thiobarbituric acid reactive substances (TBARS) assay. Results: Bisphenol A levels were significantly higher in 60 NAFLD subjects, both in urine and in plasma ( P  < 0.0001) when compared to controls and, in this group, it appeared to be higher in 30 non‐alcoholic steatohepatitis patients compared to 30 simple steatosis subjects ( P  < 0.05), independently from the presence of T2DM. After a bisphenol A‐free diet for 1 month, NAFLD patients showed a significant reduction in bisphenol A circulating levels ( P  < 0.05), without a significant reduction in urine levels. H‐HepG2 cells treated with bisphenol A (0.05 μM) increased proliferation compared to controls at 48 h ( P  < 0.0001). Bisphenol A increased TBARS levels at 48 h versus controls. Conclusions: Our study reveals a possible role of bisphenol A as an environmental factor involved in the promotion of NAFLD, particularly in T2DM patients.